The effect of vaginal cream of flaxseed and conjugated estrogen on sexual satisfaction in postmenopausal women: A single-blind randomized clinical trial - Fahimeh Shakeri; Nahid Golmakani; Seyed Reza Mazluom; Shokouhsadat Hamedi; Zohreh Feyzabadi; Nafiseh Saghafi (Mashhad University of Medical Sciences, 2023)
Introduction: Sexual satisfaction is a person's positive evaluation of the sexual relationship. Decrease in sexual satisfaction is one of the common complaints of the postmenopausal period. Flaxseed is a phytoestrogen and contains lignan. The present study was conducted with aim to investigate the effect of vaginal cream of flaxseed and conjugated estrogen on sexual satisfaction in postmenopausal women. Methods: This single-blind randomized clinical trial study was conducted in 2018-2019 on 60 married postmenopausal women aged 40 to 65 years referred to the clinics of Qaem and Imam Reza hospitals in Mashhad, Villa Shahr Health Center and the health center of Khalilabad city of Kashmar. The research units were randomly assigned in two groups of 30 people, vaginal cream of flaxseed and conjugated estrogen for 8 weeks. The intervention group received 4% vaginal gel in the form of one gram per day, and the flaxseed group received one gram per day for up to 8 weeks. Sexual satisfaction was calculated based on Larson's questionnaire before, 4 and 8 weeks after the study. Data analysis was done using SPSS statistical software (version 22) and Independent t-test, Friedman and Mann-Whitney tests. P<0.05 was considered statistically significant.Results: The mean sexual satisfaction 4 weeks after the intervention was 24.2 ± 10.4 in the flaxseed group and 23.4 ± 12.1 in the conjugated estrogen group (P=0.576), and after 8 weeks, it was 37.7 ± 18.2 in the flaxseed group and 37.8 ± 18.3 in the conjugated estrogen group, which did not show a significant difference between the two groups (P=0.638). Conclusion: Vaginal cream of flaxseed without any side effects compared to the side effects of hormone therapy can be as effective as conjugated estrogen vaginal cream in increasing sexual satisfaction.